2011
DOI: 10.1097/aog.0b013e31822200eb
|View full text |Cite
|
Sign up to set email alerts
|

Apgar Scores at 5 Minutes After Birth in Relation to School Performance at 16 Years of Age

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 20 publications
2
37
1
Order By: Relevance
“…In contrast, a number of larger and more robust studies have demonstrated increased risk of learning disability24 or special educational needs schooling14 25–27 among children with low Apgar scores at birth. These include a Norwegian birth cohort where children with a low Apgar score were more likely to have ASN and below-average educational performance, as reported by parents;14 three large linkage studies from the USA in which low Apgar score predicted later school-age ASN or learning disability;24–26 and a Swedish linkage study in which lack of graduation grades was used as a proxy for attendance at a special school 27. Another linkage study of Swedish boys reported that low Apgar scores, in the absence of overt encephalopathy, were associated with poorer results on cognitive testing but not school grades,15 which fits with our finding of no relationship between Apgar score and subsequent educational achievement.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a number of larger and more robust studies have demonstrated increased risk of learning disability24 or special educational needs schooling14 25–27 among children with low Apgar scores at birth. These include a Norwegian birth cohort where children with a low Apgar score were more likely to have ASN and below-average educational performance, as reported by parents;14 three large linkage studies from the USA in which low Apgar score predicted later school-age ASN or learning disability;24–26 and a Swedish linkage study in which lack of graduation grades was used as a proxy for attendance at a special school 27. Another linkage study of Swedish boys reported that low Apgar scores, in the absence of overt encephalopathy, were associated with poorer results on cognitive testing but not school grades,15 which fits with our finding of no relationship between Apgar score and subsequent educational achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Infants with low 5 minute Apgar scores often require respiratory support and have poorer future academic achievement. 33 Small for gestational age was defined as less than the sex-specific 10 th percentile of weight for each week of gestation within the Geisinger population from 2006-2013. While creating the a priori outcomes, we discovered that maternal and fetal specialists often use the electronic health record problem list to identify a pregnancy as high-risk.…”
Section: Methodsmentioning
confidence: 99%
“…12 13 The 5 min Apgar score is a predictor of neonatal mortality, 14 and several neurological outcomes. [15][16][17][18][19] A suboptimal fetal environment 20 related to a low Apgar score may also be associated with compromised immune responses against tumours, 21 which can predict long-term health problems, 22 23 including future cancer risk.…”
Section: Strengths and Limitation Of This Studymentioning
confidence: 99%